Nano-drug delivery method for enhancing LGP kidney targeted release and application of nano-drug delivery method

By constructing HCS-LGP NPs, the problem of low oral bioavailability of LGP is solved, and the efficacy and targeted enhancement of LGP in the treatment of chronic kidney disease is achieved.

CN119770455APending Publication Date: 2025-04-08YICHANG CENT PEOPLES HOSPITAL +1

Patent Information

Application Number
CN202411981756.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In the prior art, LGP has low oral bioavailability, resulting in less effective efficacy in treating diabetic nephropathy and requires longer treatment time.

Method used

By synthesizing hydrophobically modified chitosan polymers, HCS nanoparticles were prepared and LGP was encapsulated in the hydrophobic core of chitosan nanoparticles, and the nanodrug delivery system HCS-LGP NPs were constructed.

Benefits of technology

It improves the renal targeting and bioavailability of LGP, enhances its efficacy in the treatment of chronic kidney disease, and reduces the occurrence of adverse reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119770455A_ABST
    Figure CN119770455A_ABST
Patent Text Reader

Abstract

The invention discloses a nano-drug delivery method for enhancing LGP kidney targeted release and application of the nano-drug delivery method, and relates to the technical field of nano-drugs. According to the nano-drug delivery method for enhancing LGP kidney targeted release and the application thereof, a hydrophobic modified chitosan polymer is synthesized; preparing HCS nanoparticles; and constructing a drug loaded nanoparticle, namely, HCS-LGP NPs. According to the invention, the solubility of the medicine is increased, the distribution of the medicine in vivo is changed, and the targeting of the medicine is improved, so that the treatment effect is improved, and adverse reactions are reduced. Due to good biocompatibility and modifiability, chitosan is widely used as a nano delivery carrier of anti-tumor and antibacterial drugs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nanomedicine, and in particular to a nanomedicine delivery method for enhancing the kidney-targeted release of LGP and an application thereof. Background Art

[0002] Chronic kidney disease (CKD) is characterized by chronic renal structural and functional disorders, and its incidence rate is increasing year by year, becoming a global public health problem. Data analysis results show that in 2022, the number of adult CKD patients in China ranked first in Asia, accounting for 36.80% of the total number of adult patients in Asia, indicating that China faces a huge CKD disease burden. Therefore, effective prevention and treatment of CKD has become a research hotspot.

[0003] Currently, diabetes and hypertension are the two main causes of CKD, and other causes include infectious nephritis, renal vasculitis, ureteral obstruction, genetic variation, autoimmune diseases, and drugs. Various progressive renal diseases eventually progress to renal fibrosis, which is characterized by increased matrix production, inhibition of matrix degradation, regulation of matrix receptors to promote cell-matrix interactions, activation of mesangial cells and fibroblasts, transformation of tubular epithelial cells to mesenchymal cells, activation of myofibroblasts, infiltration and apoptosis of immune cells, etc.

[0004] Linagliptin (LGP) is a specific DPP-4 inhibitor. It was approved by the US Food and Drug Administration in 2011 for the treatment of type 2 diabetes and is clinically used alone or in combination with metformin. Its mechanism of action is to inhibit the degradation of GLP-1 and glucose-dependent insulin secretion peptide (GIP) by DPP-4, thereby increasing the concentration of active insulin secretion hormone (AIH), stimulating the release of glucose-dependent insulin, and reducing the level of glucagon in the circulation, thereby lowering blood sugar. In addition, the natural substrates of DPP-4 inhibitors also include human stromal-derived factor-1α (SDF-1α), brain natriuretic peptide (BNP) and neuropeptide Y (NPY). Studies have shown that DPP-4 inhibitors can produce a variety of biological effects in addition to regulating blood sugar. Many studies have found that LGP exhibits renal protective effects, including reducing proteinuria, glomerular sclerosis and renal interstitial fibrosis. The GLP-1 / GLP1R pathway may play a secondary role in renal protection. Studies have shown that LGP can counteract the effects of 5 / 6 nephrectomy (5 / 6Nx) by upregulating heterogeneous nuclear ribonucleoprotein A1 (HNRNPA1) and thymosin-b4, which can downregulate Y-box binding protein 1 (YB-1) and transforming growth factor β1 (TGF-β1) in the kidney independently of GLP1R. LGP attenuated peritoneal fibrosis induced by methylglyoxal (MGO) in mice, inhibited the infiltration of inflammatory cells in peritoneal tissue and the increase of TGF-β1 levels in peritoneal fluid. DPP-4 regulates the interaction of integrin β1 (ITGb1) in diabetic endothelial cells. LGP can restore the level of DPP-4 in endothelial cells to normal and directly inhibit the interaction between DPP-4 and ITGb1, thereby attenuating pathological TGF-β signaling. These studies suggest that the anti-fibrotic effect of LGP may involve blocking the abnormal expression of TGF-β1 molecules through direct or indirect pathways. Traditional drug administration is mainly oral administration and topical administration. At present, oral administration is still the most common and popular drug administration in clinical practice.

[0005] However, oral drugs have poor bioavailability, and the drug dissolution rate and cell membrane permeability during absorption are limited by their biological properties, such as water solubility and molecular weight. In addition, after oral administration, the active ingredients of the drug pass through the mouth and gastrointestinal tract, which will cause extensive chemical and physical changes, such as degradation caused by gastric acid and metabolites produced by intestinal microorganisms. It is worth noting that LGP belongs to the Biopharmaceutics Classification System (BCS) Class II drug and is a substrate of P-glycoprotein (P-gp). It has problems such as P-gp efflux, first-pass metabolism, poor permeability and systemic distribution, resulting in its low oral bioavailability (29.5%). In the diabetic nephropathy model, the combination of telmisartan + LGP significantly reduced urinary microalbumin, but the effect of LGP alone was not obvious. A phase IIIb randomized controlled double-blind clinical study on LGP showed that after 24 weeks of administration of LGP in patients with early type 2 diabetic nephropathy, blood sugar decreased and urinary microalbumin showed a downward trend but not significantly, suggesting that the renal protective effect of LGP may require a longer treatment time. It can be seen that LGP is a good candidate drug for anti-renal fibrosis, which can reduce urinary microalbumin and protect renal function, but its efficacy needs to be enhanced. Summary of the invention

[0006] In view of the deficiencies of the prior art, the present invention provides a nano drug delivery method for enhancing the kidney-targeted release of LGP and its application, which solves the problems raised in the above-mentioned background technology.

[0007] To achieve the above objectives, the present invention is implemented by the following technical scheme: a nano drug delivery method for enhancing the kidney-targeted release of LGP and its application, the method comprising the following specific steps:

[0008] S1: Synthesis of hydrophobically modified chitosan polymer (HCS);

[0009] S2: Preparation of HCS nanoparticles;

[0010] S3: Construction of drug-loaded nanoparticles—HCS-LGP NPs.

[0011] A further improvement of the technical solution of the present invention is that the chemical synthesis route for synthesizing the hydrophobically modified chitosan polymer in S1 comprises:

[0012] S1.1:

[0013]

[0014] Among them, CS is low molecular weight chitosan, SAA is succinic anhydride, and NCS is N-succinyl chitosan.

[0015] A further improvement of the technical solution of the present invention is that the chemical synthesis route for synthesizing the hydrophobically modified chitosan polymer in S1 further includes:

[0016] S1.2:

[0017]

[0018] Among them, SDM is sulfadimethoxypyrimidine and HCS is hydrophobically modified chitosan.

[0019] The further improvement of the technical solution of the present invention is that: the synthesis of the hydrophobically modified chitosan polymer includes the following specific operation steps;

[0020] Accurately weigh 0.5 g of low molecular weight chitosan, dissolve it in 15 mL of 5% acetic acid solution, dilute it to 20 mL of dimethyl sulfoxide, add succinic anhydride to the low molecular weight chitosan solution at a molar ratio of 1:4, stir it in a constant temperature magnetic stirrer to obtain N-succinyl chitosan, add sulfadimethoxypyrimidine in a molar ratio of 1:0.3 to the low molecular weight chitosan to the obtained N-succinyl chitosan solution, continue to react in a 60°C oil bath for 24 hours, use 1-ethyl-carbodiimide hydrochloride as a catalyst, then cool to room temperature, dialyze with a dialysis bag with a molecular weight cutoff of 8,000-14,000Da for 4 days, and freeze-dry the dialyzed liquid to obtain hydrophobically modified chitosan.

[0021] A further improvement of the technical solution of the present invention is that the selection of low molecular weight chitosan includes the following settings:

[0022] The low molecular weight chitosan is alkali treated, and the low molecular weight chitosan is dried.

[0023] The technical solution of the present invention is further improved in that the environment settings of the constant temperature magnetic stirrer are: ambient temperature 60°C, stirring time 24h, stirring speed 4000r / min.

[0024] A further improvement of the technical solution of the present invention is that the preparation of the HCS nanoparticles in S2 comprises the following specific steps:

[0025] Accurately weigh 50 mg of hydrophobically modified chitosan and place it in a 150 mL beaker. Add 50 mL of phosphate buffer solution with a pH of 9.18. Stir vigorously for 24 h in an oil bath at 37 °C to obtain a nearly transparent light yellow solution. Treat it with a 300 W ultrasonic grinder for 6 min. Filter the solution through a filter membrane with a pore size of 0.45 μm to remove the precipitate. The treated sample is freeze-dried to obtain an HCS nanoparticle sample.

[0026] A further improvement of the technical solution of the present invention is that the construction of the nano drug delivery system in S3 includes:

[0027] Accurately weigh 50 mg of hydrophobically modified chitosan nanoparticles, dissolve in 50 mL of pH 9.18 phosphate buffer solution, stir for 30 min to activate, weigh 5 mg of linagliptin (LGP), completely dissolve with an appropriate amount of dimethyl sulfoxide, add to the activation solution, stir at room temperature for 12 h, after stirring, transfer the mixture to a beaker, and ultrasonicate three times with a 300 W power ultrasonic disperser, 2 minutes each time, 1 second interval. The dispersion was filtered with a 0.45 μm filter membrane to obtain drug-loaded nanoparticles-HCS-LGP NPs.

[0028] A further improvement of the technical solution of the present invention is that the drug-loaded nanoparticles, HCS-LGP NPs, are freeze-dried, weighed, and labeled and then stored in a refrigerator at 4°C.

[0029] The drug-loaded nanoparticles prepared according to the method of the present invention include applications in preparing drugs for preventing and / or treating chronic kidney disease.

[0030] Beneficial Effects

[0031] The present invention provides a nano drug delivery method for enhancing the kidney-targeted release of LGP and its application. Compared with the prior art, it has the following beneficial effects:

[0032] The nano drug delivery method for enhancing the kidney-targeted release of LGP and its application, by grafting the hydrophobic compound sulfadimethoxypyrimidine on low molecular weight chitosan, successfully prepared a hydrophobically modified chitosan polymer, and characterized it by infrared spectroscopy and nuclear magnetic resonance hydrogen spectrum, the amphiphilic chitosan polymer self-assembled in water to form blank chitosan nanoparticles, and then LGP was encapsulated in the hydrophobic core of the chitosan nanoparticles, and the nano drug delivery system HCS-LGPNPs was successfully constructed, and its drug loading rate was (7.5±0.2)%;

[0033] By increasing drug solubility, changing drug distribution in the body, and improving drug targeting, the therapeutic effect is improved and the occurrence of adverse reactions is reduced. Chitosan is widely used as a nano-delivery carrier for anti-tumor and antibacterial drugs due to its good biocompatibility and modifiability. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 Flow chart of the nanodrug delivery method for enhancing kidney-targeted release of LGP;

[0035] Figure 2 FT-IR and 1H NMR spectrum analysis diagram of HCS polymer;

[0036] Figure 3 The images are potential measurements and transmission electron microscope observations;

[0037] Figure 4Draw the standard curve of gliptin and calculate the drug loading rate

[0038] Figure 5 is the in vitro drug release curve of nanoparticles;

[0039] Figure 6 This is an inverted fluorescence microscope observation image;

[0040] Figure 7 It is a bar graph of cell viability determination of HK-2 cells;

[0041] Figure 8 The bar graph shows the increase in the expression of TGF-β1 protein and collagen I protein;

[0042] Fig. 9 Figure 2 is the body weight change and serum urea nitrogen level of rats during the administration period;

[0043] Fig.10 is the fluorescence distribution map of kidney after HCS-LGP NPs;

[0044] Fig.11 H&E staining of rat heart, liver, spleen and lung by HCS-LGP NPs;

[0045] Fig.12 This is a histopathological staining image of kidney tissue;

[0046] Fig.13 This is the immunohistochemical detection image of rat kidney tissue. DETAILED DESCRIPTION

[0047] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0048] The present invention provides a nano drug delivery method for enhancing the kidney-targeted release of LGP, the method comprising the following specific steps:

[0049] S1: Synthesis of hydrophobically modified chitosan polymer (HCS);

[0050] S2: Preparation of HCS nanoparticles;

[0051] S3: Construction of drug-loaded nanoparticles—HCS-LGP NPs.

[0052] The hydrophobic compound sulfadimethoxypyrimidine (SDM) was grafted onto low molecular weight chitosan to successfully prepare hydrophobically modified chitosan polymers, which were characterized by infrared spectroscopy and nuclear magnetic resonance hydrogen spectrum. The amphiphilic chitosan polymers self-assembled in water to form blank chitosan nanoparticles, and then LGP was encapsulated in the hydrophobic core of the chitosan nanoparticles to successfully construct a nanodrug delivery system HCS-LGP NPs.

[0053] The chemical synthesis route for synthesizing the hydrophobically modified chitosan polymer in S1 includes:

[0054] S1.1:

[0055]

[0056] Among them, CS is low molecular weight chitosan, SAA is succinic anhydride, and NCS is N-succinyl chitosan.

[0057] The chemical synthesis route for synthesizing hydrophobically modified chitosan polymers in S1 also includes:

[0058] S1.2:

[0059]

[0060] Among them, SDM is sulfadimethoxypyrimidine and HCS is hydrophobically modified chitosan.

[0061] The synthesis of hydrophobically modified chitosan polymer includes the following specific steps:

[0062] Accurately weigh 0.5 g of low molecular weight chitosan, dissolve it in 15 mL of 5% acetic acid solution, dilute it to 20 mL of dimethyl sulfoxide, add succinic anhydride to the low molecular weight chitosan solution at a molar ratio of 1:4, stir it in a constant temperature magnetic stirrer to obtain N-succinyl chitosan, add sulfadimethoxypyrimidine in a molar ratio of 1:0.3 to the low molecular weight chitosan to the obtained N-succinyl chitosan solution, continue to react in a 60°C oil bath for 24 hours, use 1-ethyl-carbodiimide hydrochloride as a catalyst, then cool to room temperature, dialyze with a dialysis bag with a molecular weight cutoff of 8,000-14,000Da for 4 days, and freeze-dry the dialyzed liquid to obtain hydrophobically modified chitosan.

[0063] The selection of low molecular weight chitosan includes the following settings:

[0064] The low molecular weight chitosan is alkali treated, and the low molecular weight chitosan is dried.

[0065] The environmental settings of the constant temperature magnetic stirrer are: ambient temperature 60°C, stirring time 24h, and stirring speed 4000r / min.

[0066] The preparation of HCS nanoparticles in S2 includes the following specific steps:

[0067] Accurately weigh 50 mg of hydrophobically modified chitosan and place it in a 150 mL beaker, add 50 mL of phosphate buffer solution with pH = 9.18, and vigorously stir for 24 h in an oil bath at 37°C to obtain a nearly transparent light yellow solution. Treat it with a 300 W power ultrasonic grinder for 6 min, and filter the solution through a filter membrane with a pore size of 0.45 μm to remove the precipitate. The treated sample is freeze-dried to obtain a hydrophobically modified chitosan polymer nanoparticle sample.

[0068] The construction of nano drug delivery system in S3 includes:

[0069] Accurately weigh 50 mg of hydrophobically modified chitosan nanoparticles, dissolve in 50 mL of pH 9.18 phosphate buffer solution, stir for 30 min to activate, weigh 5 mg of linagliptin (LGP), completely dissolve with an appropriate amount of dimethyl sulfoxide, add to the activation solution, stir at room temperature for 12 h, after stirring, transfer the mixture to a beaker, and ultrasonicate three times with a 300 W power ultrasonic disperser, 2 minutes each time, 1 second interval. The dispersion was filtered with a 0.45 μm filter membrane to obtain drug-loaded nanoparticles-HCS-LGP NPs.

[0070] The drug-loaded nanoparticles, HCS-LGP NPs, were freeze-dried, weighed, labeled, and stored in a refrigerator at 4°C.

[0071] Example 1, to verify whether the synthesis reaction of the hydrophobically modified chitosan polymer is successful, 50 mg of hydrophobically modified chitosan is accurately weighed and placed in a 150 mL beaker, 50 mL of a phosphate buffer solution with a pH of 9.18 is added, and the mixture is vigorously stirred for 24 h in an oil bath at 37°C to obtain a nearly transparent light yellow solution, which is treated with a 300 W power ultrasonic grinder for 6 min, and the solution is filtered within a filter membrane with a pore size of 0.45 μm to remove the precipitate, and the treated sample is freeze-dried to obtain a hydrophobically modified chitosan polymer nanoparticle sample, and then the hydrophobically modified chitosan polymer is subjected to FT-IR and 1H NMR spectral analysis;

[0072] like Figure 2 As shown in A, in the CS infrared spectrum, 1624cm-1 is the bending vibration peak of the primary amine; in the HCS infrared spectrum, this peak disappears, and new absorption peaks at 1727cm-1 (νc=o), 1660cm-1 (amide I) and 1560cm-1 (amide II) appear, indicating the formation of an amide bond. The above results show that succinic anhydride has been successfully grafted. New absorption peaks appear at 1147cm-1 and 837cm-1 in the HCS infrared spectrum, which are the stretching vibration peaks of the methoxy group in sulfadimethoxypyrimidine and the bending vibration peaks of the para-substituted benzene ring, respectively, indicating the successful grafting of sulfadimethoxypyrimidine. Figure 2 As shown in Figure B, there are significant differences in the hydrogen nuclear magnetic resonance spectra of CS and HCS. The small signal at 4.50ppm belongs to the amide bond formed in the reaction, indicating the successful grafting of succinic anhydride. The small signal at 4.50ppm belongs to the amide proton (-NH-COCH2CH2COOH), the peak at 7.6ppm is the characteristic peak of H on the benzene ring in SDM, and the peak at 5.7ppm is the characteristic peak of H on the pyrimidine ring in SDM. In addition, due to chemical grafting, some other peaks have slight shifts and changes in intensity. The 1H NMR results are consistent with the FT-IR results, indicating that the synthesis reaction of HCS is successful, thereby proving the successful synthesis of the hydrophobically modified chitosan polymer HCS of the present application.

[0073] Example 2, after the successful synthesis of HCS polymer, blank nanoparticles were prepared by self-assembly method, and then LGP was loaded by water dialysis. 5 mg of HCS nanoparticles and HCS-LGP nanoparticles were weighed, dissolved in deionized water, filtered with a 0.45 μm filter membrane and loaded into a cuvette, and the particle size and polydispersity index were detected by a laser particle size analyzer. The potential was detected with a potentiometer. All samples were repeated three times. A small amount of HCS-LGP nanoparticle solution was dropped on a copper mesh coated with a carbon support film. After natural drying, the morphology and particle size were observed using a HT7800 transmission electron microscope.

[0074] like Figure 3 As shown in A and 3C, the particle size of HCS NPs is about 134.9 nm and the potential is -mV. Due to the loading of linagliptin, the particle size of HCS-LGP NPs increases to 178.8 nm and the potential increases to -29.9 mV ( Figure 3 B and 3D). Transmission electron microscopy showed that the drug-loaded nanoparticles were uniformly spherical with a particle size of about 50-100 nm. Figure 3 E. The above results show that drug-loaded nanoparticles with negative potential, spherical shape and particle size in the range of 100-200 nm were successfully prepared.

[0075] Example 3, the drug loading rate and encapsulation rate of the drug-loaded nanoparticles prepared in this application are calculated, a small amount of Linagliptin is dissolved and diluted with DMSO, poured into a cuvette, and scanned with a UV spectrophotometer in the wavelength range of 200-360nm, and the data is recorded to determine the maximum absorption wavelength. Another 40mg of Linagliptin is dissolved in an appropriate amount of DMSO, transferred to a 10mL volumetric flask, and diluted with DMSO to a concentration of 5, 10, 20, 40, 60μg / mL. Take an appropriate amount of Linagliptin solution with different concentration gradients and put it into a cuvette, adjust the blank control to zero with DMSO, measure three times in parallel, and record the absorbance value of the sample. 50 mg of HCS nanoparticles were dissolved in 50 mL of PBS at pH 9.18, 5 mg of linagliptin was weighed and dissolved in DMSO solution, the two solutions were mixed, and stirred at room temperature for 12 h to obtain drug-loaded nanoparticles. After the nanoparticles were freeze-dried, an appropriate amount of nanoparticles was dissolved in an aqueous solution, and the ultraviolet absorbance at 300 nm was measured. The measurement was repeated three times, and the calculation formula is as follows:

[0076] Drug loading rate (%) = drug weight in nanoparticles / total weight of nanoparticles × 100%

[0077] Scan the spectrum of LGP standard solution in the range of 200-360nm using a UV spectrophotometer, such as Figure 4 As shown in A, the maximum absorption wavelength of LGP is 300nm. Use a UV spectrophotometer to measure the absorbance of a series of LGP standard solutions with different concentrations (5, 10, 20, 40, 60μg / mL) at 300nm and draw a standard curve. Figure 4 As shown in B, the standard curve equation was calculated as y = 0.036x + 0.0693, and the correlation coefficient R2 = 0.9963, indicating that the concentration of LGP and the absorbance showed a good linear relationship within the selected concentration range. According to the standard curve equation, the drug loading rate of HCS-LGP NPs was calculated to be (7.5 ± 0.2)%.

[0078] After verifying the drug loading rate, the in vitro release behavior of drug-loaded nanoparticles was studied. 2 mg of Linagliptin was dissolved in 5 mL of PBS buffer solution, transferred to a dialysis bag, and placed in a beaker containing 80 mL of pH 5.4 PBS buffer solution. 10 mg of drug-loaded nanoparticles was dissolved in 10 mL of PBS buffer solution, divided into two portions of 5 mL each, and loaded into dialysis bags with a molecular weight cutoff of 3500 Da. The dialysis bags were then placed in beakers containing 80 mL of PBS buffer solutions with different pH values ​​(pH = 7.4 and pH = 5.4) and placed in a constant temperature shaker at 37 ° C and 100 rpm to simulate the in vivo environment. Oscillate at 37 ° C and 100 rpm in a constant temperature shaker, away from light. Samples were taken at regular intervals (Tn, n = 0, 0.5, 1, 2, 4, 8, 24, 48 h), 5 mL of release medium was collected, and an equal volume of PBS buffer was added. The absorbance of the solution was measured with a UV spectrophotometer to determine the amount of drug released. PBS buffer solutions with different pH values ​​were used to simulate the normal physiological environment in vivo and the acidic environment of renal fibrosis inflammation to study the in vitro drug release of nanoparticles. Figure 5 As shown in the results, the free drug was almost completely released in an acidic environment of pH 5.4 within 24 hours. At pH 7.4, the release rate of levofloxacin within 48 hours was (36.33±1.53)%, while in an acidic environment of pH 5.4, the drug release rate reached (44.33±1.15)%. The above results show that HCS-LGP NPs have certain acid sensitivity and sustained release effects compared with LGP, suggesting that after being transported to the kidneys, the nanoparticles exert a sustained therapeutic effect through sustained release in the acidic environment of renal fibrosis.

[0079] Example 4, the efficacy of HCS-LGP NPs and the effectiveness of treating renal fibrosis were verified, including the following verification steps, T1: cell uptake; T2: cell viability test; T3: Western blot test; T4: establishment of rat renal fibrosis model and drug administration; T5: kidney targeting study; T6: determination of biochemical indicators of rat renal function; T7: histopathological examination; T8: immunohistochemical examination of renal tissue.

[0080] When HK-2 cells grew to the logarithmic growth phase, they were seeded in a confocal culture dish at a density of 2×10^5 cells / well. After overnight culture, they were incubated with free FITC and FITC-labeled HCS-LGP NPs for 5 hours. The cells were washed three times with PBS buffer, fixed with 4% (v / v) paraformaldehyde for 10 minutes, and then washed with PBS. Subsequently, they were stained with 1 mL DAPI for 10 minutes, washed three times with PBS, and finally photographed with an inverted fluorescence microscope (CLSM).

[0081] The uptake of free FITC and FITC-labeled HCS-LGP NPs in the TGF-β1-induced HK-2 cell fibrosis model was observed by inverted fluorescence microscopy. FITC showed green fluorescence and DAPI showed blue fluorescence. After incubation at 37°C for 5 hours, weak green fluorescence was observed in the free FITC group, while the green fluorescence of the nanoparticle group was significantly enhanced, indicating that HK-2 cells successfully took up a large amount of HCS-LGP NPs ( Figure 6 ). By quantitative fluorescence analysis of uptake statistics, the uptake efficiency of nanoparticles by HK-2 cells was significantly higher than that of the free FITC group. The above results indicate that chitosan nanoparticle encapsulation increases the uptake of drugs by HK-2 cells, which may be due to the similar aminoglycoside structure of chitosan and the ligand of Megalin receptor, which is highly expressed in renal tubular epithelial cells, so HK-2 cells can mediate the endocytosis of nanoparticles.

[0082] Among them, T2: In the cell viability test, the MTT method was used to detect the cytotoxicity of free drugs and nanoparticles. HK-2 cells in the logarithmic growth phase were seeded in a 96-well plate at 5×10^3 cells / well and 100μL volume. After attachment, they were divided into a control group, an LGP group, an HCS NPs group, and an HCS-LGP NPs group. Then, TGF-β1 (20ng / mL) was used to induce fibrosis, and then incubated with the corresponding drugs for 24h. 20μL of 5mg / mL MTT solution was added to each well and incubated in a 37℃ incubator for 4h. Subsequently, the free drugs and nanoparticles in the 96-well plate were removed with a pipette. 5mg / mL MTT solution was added to each well and incubated in a 37℃ incubator for 4h. Subsequently, the solution was removed from the 96-well plate with a pipette, 150μL DMSO was added to each well to dissolve the formazan, and the plate was placed on a shaker for 15min, and the absorbance (OD) was measured at a wavelength of 490nm using an enzyme reader.

[0083] T3: Total protein of HK-2 cells was collected after administration in Western blot test, and the total protein concentration of each experimental group was determined by BCA protein quantification kit. Equal amounts of protein samples were separated by SDS polyacrylamide gel electrophoresis and transferred to PVDF membrane. After blocking with 5% skim milk powder for 1 hour, the PVDF membrane was incubated with corresponding primary and secondary antibodies for a specified time. Protein bands were detected using ECL reagent and imaging system.

[0084] The occurrence of fibrosis is usually associated with the overactivation of TGF-β1, and the increased expression of TGF-β1 leads to collagen deposition. Therefore, TGF-β1 and collagen I were selected as indicators of fibrosis to verify the successful establishment of the renal fibrosis model and to explore the in vitro anti-renal fibrosis effect of LGP and HCS-LGP NPs. Figure 8As shown in the figure, after TGF-β1 stimulation, the expression of TGF-β1 protein and collagen I protein in HK-2 cells was significantly increased, while after the administration of LGP and HCS-LGP NPs, the expression of these two proteins was significantly decreased, among which the inhibitory effect of the HCS-LGP NPs group was more significant.

[0085] Among them, T4: Establishment of rat renal fibrosis model and drug administration, 30 male SPF-grade SD rats (weight 190-230g, 5-6 weeks old) were selected as experimental subjects, and after one week of quarantine, they were transferred to the animal culture room for subsequent experiments. First, a renal fibrosis rat model was constructed. Except for the normal control group, the model group and each drug-treated group were given adenine by gavage (200mg / kg, once a day, for 4 consecutive weeks), and the normal control group was given an equal amount of 0.5% CMC-Na by gavage. After successful modeling, each drug-treated group was injected with 200uL of physiological saline solution containing the corresponding drug (i.e., free LGP and HCS-LGP NPs) through the tail vein. The LGP dose was 3mg / kg, and it was administered once every two days for a total of 14 days.

[0086] The body weight changes of rats during the administration period were as follows Fig. 9 As shown in A. Since the control group was not given adenine for modeling, the rats grew normally and weighed more than the model group, LGP group and HCS-LGP NPs group. The model group, LGP group and HCS-LGP NPs group were affected by renal fibrosis and had a lighter body weight. After the adenine gavage was stopped during the administration period, the body weight gradually increased, among which the weight gain in the HCS-LGPNPs group was the most significant. Serum creatinine (Scr) and urea nitrogen (BUN) levels are classic indicators of renal function. In order to study the therapeutic effect of nanoparticles on renal fibrosis, we constructed a renal fibrosis rat model and collected serum creatinine and urea nitrogen from each group for analysis after administration. As shown Fig. 9 As shown in B, after 14 days of administration, the serum urea nitrogen level in the model group was significantly higher than that in the normal control group. Compared with the model group, the serum urea nitrogen level in the free LGP group was reduced, and the serum urea nitrogen level in the HCS-LGP NPs group was significantly reduced. Fig. 9 As shown in C, compared with the normal control group, the serum creatinine level in the model group was significantly increased, and compared with the model group, the serum creatinine levels in the free LGP group and the HCS-LGP NPs group were decreased, and the serum creatinine level in the HCS-LGP NPs group was significantly decreased.

[0087] Among them, T5: In the kidney targeting study, FITC was used as a fluorescent indicator to label HCS-LGP NPs, and the model rats were divided into a free FITC group and a FITC-labeled HCS-LGP NPs group, and each group was injected with 200 μL through the tail vein. After injection, the rats were killed at different time points (2, 8, 24h), and the kidneys and other major organs (heart, liver, spleen, lungs) were collected, and the fluorescence distribution of each organ was observed using a small animal in vivo imaging system.

[0088] Free FITC and FITC-labeled HCS-LGP NPs were injected via the tail vein, and the distribution of free FITC and FITC-labeled HCS-LGP NPs in the kidney was observed at 2h, 8h and 24h using a small animal in vivo fluorescence imaging system. Fig.10 A shows the fluorescence imaging of normal and fibrotic rats 24 h after tail vein injection of free FITC and FITC-labeled HCS-LGP NPs. The fluorescence imaging results of free FITC and FITC-labeled HCS-LGP NPs in the kidneys of control and fibrotic rats showed that the uptake of FITC-labeled HCS-LGP NPs in the kidneys was higher compared with free FITC, indicating that the accumulation of FITC in the kidneys was increased due to the loading of nanoparticles. The accumulation of free FITC and nanoparticles in fibrotic kidneys was significantly increased compared with the control group, which may be due to the reduced excretion and increased drug accumulation caused by renal lesions. Fig.10 B shows the renal fluorescence distribution of rats with renal fibrosis after injection of free FITC and FITC-labeled HCS-LGP NPs at 2h, 8h, and 24h. The images show that the free FITC group and the FITC-labeled HCS-LGP NPs group began to accumulate in the kidney at 2h. The fluorescence intensity of the free FITC group was the strongest at 8h, and the fluorescence gradually disappeared after 24h. The fluorescence intensity of the FITC-labeled HCS-LGP NPs group gradually increased from 2h to 24h, indicating that the nanoparticles have a certain sustained release effect and prolong the retention time of the drug in the kidney. Fig.10 C shows the fluorescence imaging of the heart, liver, spleen, lung and kidney of rats 2h, 8h and 24h after tail vein injection of free FITC and FITC-labeled HCS-LGP NPs. The results showed that the free FITC group accumulated in the heart, liver, spleen and lung to varying degrees, with more accumulation in the kidney compared with the kidney, while the FITC-labeled HCS-LGP NPs group accumulated significantly more in the kidney than in other tissues and organs. The above results show that HCS-LGP NPs have certain renal targeting, with specific distribution, longer retention time and sustained release, suggesting that HCS-LGP NPs may have good biosafety and improve the therapeutic effect of LGP through renal targeting.

[0089] Among them, T6: In the determination of biochemical indicators of rat renal function, the blood urea nitrogen (BUN) and serum creatinine (SCr) levels were determined using a fully automatic biochemical analyzer.

[0090] Among them, T7: In histopathological examination, after the rats were killed, heart, liver, spleen, lung and kidney tissues were collected for morphological analysis. Tissue samples were fixed with 4% paraformaldehyde (PFA) and then embedded in paraffin. Paraffin sections were dewaxed with xylene and dehydrated with ethanol, and heart, liver, spleen and lung tissues were stained with hematoxylin and eosin (H&E) to evaluate the biocompatibility of nanoparticles. Kidney sections were stained with H&E and Masson to evaluate renal injury and collagen deposition, respectively, and image analysis software (Image J) was used for semi-quantitative calculation of staining area.

[0091] Among them, T8: In the immunohistochemistry test of renal tissue, 4 μm thick renal tissue sections were subjected to IHC staining to detect the expression of TGF-β1 and collagen I. The primary antibodies used were: TGF-β1 mouse polyclonal antibody and collagen I rabbit monoclonal antibody. The content of the target protein was determined by observing the staining color depth and staining area, and the average optical density value of each group of images was analyzed using ImageJ software.

[0092] To investigate the effects of HCS-LGP NPs on the major organs of rats, H&E staining was performed on the heart, liver, spleen, and lungs of rats. Fig.11 As shown, the heart, liver, spleen and lung cells of the control group, model group and HCS-LGP NPs group were intact and tightly connected, indicating that the nanoparticles did not damage normal tissues in vivo, while the liver of the LGP group was damaged. The liver damage in the LGP group may be due to the increased metabolic burden on the liver caused by multiple administrations, resulting in a certain degree of liver damage. The above results show that the prepared nano drug delivery system exhibits good biocompatibility.

[0093] The effects of nanoparticles on fibrotic kidneys were evaluated by H&E staining and Masson staining. Fig.12 As shown in A, the H&E staining results of rat renal tissue sections showed that there were no significant histopathological changes in the control group, while the rats in the model group had disordered glomerular structure, obvious periglomerular fibrosis, and obvious tubular dilatation; compared with the model group, the renal damage of rats in each group was significantly restored, among which the effect of nanoparticles in the control group was more significant than that of free drugs. Fig.12B shows the Masson staining results of rat renal tissue sections. The results showed that only a small amount of collagen fiber deposition was found around the glomeruli and tubules in the renal tissue of rats in the control group, while the amount of blue collagen fiber deposition around the glomeruli and tubules in the renal tissue of rats in the model group was significantly increased compared with the normal control group; the blue staining area in the drug-treated group was significantly reduced, and the statistical results showed that the nanoparticle group was more effective in preventing fibrosis. These results indicate that the efficacy of LGP has been enhanced by nanoparticle loading.

[0094] In immunohistochemical analysis, the effects of LGP and HCS-LGP NPs on the expression of collagen I and TGF-β1 in renal tissue were further investigated. Fig.13 As shown in A, LGP and HCS-LGP NPs groups significantly downregulated the level of TGF-β1 protein in the kidneys of rats with renal fibrosis, among which the downregulation in the HCS-LGP NPs group was more significant. Fig.13 B shows the immunohistochemistry results of collagen I in rat renal tissue sections. The model group showed a significant increase in the brown staining area around the renal tubules and glomeruli; compared with the model group, the brown staining area in the LGP group and HCS-LGP NPs group was significantly reduced. The above results indicate that LGP and HCS-LGP NPs can reduce the deposition of collagen I and TGF-β1 protein in renal tissue after renal fibrosis, and the effect of the HCS-LGP NPs group is more significant.

[0095] As mentioned above, by grafting the hydrophobic compound sulfadimethoxypyrimidine on low molecular weight chitosan, an amphiphilic chitosan polymer was successfully prepared and characterized by infrared spectroscopy and nuclear magnetic resonance hydrogen spectrum. The amphiphilic chitosan polymer self-assembled in water to form blank chitosan nanoparticles, and then LGP was encapsulated in the hydrophobic core of chitosan nanoparticles to successfully construct a nano drug delivery system HCS-LGP NPs, with a drug loading rate of (7.5±0.2)%.

[0096] The average hydrated particle size and potential of the prepared drug-loaded nanoparticles were measured by dynamic light scattering (DLS) to be 178.8 nm and -29.9 ± 0.7 mV, respectively. Transmission electron microscopy (TEM) observation showed that the prepared drug-loaded nanoparticles had a particle size of about 50-100 nm and a uniform spherical shape. In vitro drug release studies showed that the release efficiency of HCS-LGP NPs in PBS buffer solutions of pH = 5.4 and pH = 7.4 for 48 h was 44.33% and 36.33%, respectively. Within the first 10 h, the rapid release of LGP ensured that the nanoparticles quickly reached an effective concentration in the renal tissue. The slow release within 10 h-48 h showed a good sustained release effect, which was conducive to achieving a lasting anti-fibrotic effect in the renal tissue.

[0097] Therefore, this application studies the in vitro anti-renal fibrosis effect of the nano-delivery system HCS-LGP NPs. MTT results showed that the blank nanocarrier had good biocompatibility, and HCS-LGP NPs had no obvious cytotoxicity below a concentration of 5 μg / mL; cell uptake experiments showed that the uptake efficiency of HCS-LGP NPs in HK-2 cells was significantly higher than that of free FITC, which may be due to the fact that the aminoglycoside structure of chitosan is similar to the ligand of the Megalin receptor and can be internalized by the Megalin receptor. The significant uptake of nanoparticles by HK-2 cells indicates that nano-drug preparations may be more effective in the treatment of renal fibrosis, and nanocarriers can make drugs more frequently taken up by cells and exert a stronger anti-renal fibrosis effect. The in vitro anti-renal fibrosis effect of LGP and HCS-LGP NPs was studied by Western blot experiments, and the results showed that HCS-LGP NPs significantly inhibited the overexpression of TGF-β1 and collagen I protein in the HK-2 cell fibrosis model.

[0098] Animal experiments showed that the constructed nanodelivery system can accumulate in the kidney and play a role in sustained drug release. H&E staining of the heart, liver, spleen and lungs showed that HCS-LGP NPs had good biocompatibility. Fluorescence imaging studies of the kidney showed that the fluorescence intensity of the HCS-LGP NPs group in the kidney was higher than that of the free FITC group, and the accumulation in the kidney was significantly higher than that in other major organs. The targeting effect of HCS-LGP NPs on the kidney significantly improved its anti-renal fibrosis efficiency. In the study of the in vivo anti-renal fibrosis effect, a rat renal fibrosis model was successfully constructed. The results of serum creatinine, urea nitrogen and renal tissue collected 14 days after administration showed that the serum creatinine and urea nitrogen levels in the model group were significantly increased, while those in the HCS-LGPNPs group were significantly decreased compared with the LGP group. The results of H&E staining and Masson staining of the kidney showed that the degree of renal fibrosis was reduced after administration, and the degree of structural damage of the glomeruli and tubules was reduced. Due to the targeting of the nanoformulation, the anti-renal fibrosis effect of the nanodelivery system was better than that of the free drug. At the same time, the immunohistochemistry results of fibrotic kidneys showed that the nanoformulation significantly reduced the excessive deposition of TGF-β1 and collagen I protein.

[0099] Therefore, the nanoparticles are released faster in an acidic environment and can be effectively absorbed by HK-2 cells, which has a strong inhibitory effect on cell growth and can significantly inhibit the expression of TGF-β1 protein and collagen I. Animal experiments further confirmed the targeting effect of nanoparticles on the kidneys, which can significantly reduce serum urea nitrogen levels and creatinine levels without obvious side effects.

[0100] Meanwhile, the contents not described in detail in this specification belong to the prior art known to those skilled in the art, and the model parameters of each electrical appliance are not specifically limited, and conventional equipment can be used.

[0101] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0102] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A nano drug delivery method for enhancing the kidney-targeted release of LGP, characterized in that: The method comprises the following specific steps: S1: Synthesis of hydrophobically modified chitosan polymer; S2: Preparation of HCS nanoparticles; S3: Construction of drug-loaded nanoparticles—HCS-LGP NPs.

2. A nano drug delivery method for enhancing the kidney-targeted release of LGP according to claim 1, characterized in that: The chemical synthesis route for synthesizing the hydrophobically modified chitosan polymer in S1 includes: S1.1: Among them, CS is low molecular weight chitosan, SAA is succinic anhydride, and NCS is N-succinyl chitosan.

3. A nano drug delivery method for enhancing the kidney-targeted release of LGP according to claim 1, characterized in that: The chemical synthesis route for synthesizing the hydrophobically modified chitosan polymer in S1 also includes: S1.2: Among them, SDM is sulfadimethoxypyrimidine and HCS is hydrophobically modified chitosan.

4. A nano drug delivery method for enhancing the kidney-targeted release of LGP according to claim 2, characterized in that: The synthesis of hydrophobically modified chitosan polymer includes the following specific steps: Accurately weigh 0.5 g of low molecular weight chitosan, dissolve it in 15 mL of 5% acetic acid solution, dilute it to 20 mL of dimethyl sulfoxide, add succinic anhydride to the low molecular weight chitosan solution at a molar ratio of 1:4, stir it in a constant temperature magnetic stirrer to obtain N-succinyl chitosan, add sulfadimethoxypyrimidine in a molar ratio of 1:0.3 to the low molecular weight chitosan to the obtained N-succinyl chitosan solution, continue to react in a 60°C oil bath for 24 hours, use 1-ethyl-carbodiimide hydrochloride as a catalyst, then cool to room temperature, dialyze with a dialysis bag with a molecular weight cutoff of 8,000-14,000Da for 4 days, and freeze-dry the dialyzed liquid to obtain hydrophobically modified chitosan.

5. A nano drug delivery method for enhancing the kidney-targeted release of LGP according to claim 4, characterized in that: The selection of low molecular weight chitosan includes the following settings: The low molecular weight chitosan is alkali treated, and the low molecular weight chitosan is dried.

6. A nano drug delivery method for enhancing the kidney-targeted release of LGP according to claim 4, characterized in that: The environmental settings of the constant temperature magnetic stirrer are: ambient temperature 60°C, stirring time 24h, and stirring speed 4000r / min.

7. A nano drug delivery method for enhancing the kidney-targeted release of LGP according to claim 1, characterized in that: The preparation of HCS nanoparticles in S2 comprises the following specific steps: Accurately weigh 50 mg of hydrophobically modified chitosan and place it in a 150 mL beaker. Add 50 mL of phosphate buffer solution with a pH of 9.

18. Stir vigorously for 24 h in an oil bath at 37 °C to obtain a nearly transparent light yellow solution. Treat it with a 300 W ultrasonic grinder for 6 min. Filter the solution through a filter membrane with a pore size of 0.45 μm to remove the precipitate. The treated sample is freeze-dried to obtain an HCS nanoparticle sample.

8. A nano drug delivery method for enhancing the kidney-targeted release of LGP according to claim 1, characterized in that: The construction of the nano drug delivery system in S3 includes: Accurately weigh 50 mg of hydrophobically modified chitosan nanoparticles, dissolve in 50 mL of pH 9.18 phosphate buffer solution, stir for 30 min to activate, weigh 5 mg of linagliptin, dissolve it completely with an appropriate amount of dimethyl sulfoxide, add it to the activation solution, stir at room temperature for 12 h, and after stirring, transfer the mixture to a beaker and sonicate it three times with a 300 W power ultrasonic disperser, 2 minutes each time, 1 second interval. The dispersion was filtered with a 0.45 μm filter membrane to obtain drug-loaded nanoparticles - HCS-LGP NPs.

9. A nano drug delivery method for enhancing the kidney-targeted release of LGP according to claim 8, characterized in that: The drug-loaded nanoparticles, HCS-LGP NPs, were freeze-dried, weighed, labeled, and stored in a refrigerator at 4°C.

10. Drug-loaded nanoparticles prepared according to the method according to any one of claims 1 to 9, including use in preparing drugs for preventing and / or treating chronic kidney disease.

Citation Information

Patent Citations

  • Chitosan derivative nano particle as well as medicine carrying nano particle and preparation method thereof

    CN103877585A

  • Linagliptin long-acting sustained-release microsphere and preparation method thereof

    CN116407509A

Cited By

  • Fibrosis microenvironment response polymer, drug-entrapped nanoparticles prepared from polymer, and preparation method and application of drug-entrapped nanoparticles

    CN121800969A

  • Composite targeted drug for treating renal fibrosis and preparation process thereof

    CN122182816A